IDENTIFICATION OF MERCURY CONTENT IN SMALLHOLDER GOLD MINING WELL WATER IN THE WORKING AREA OF UPTD PUSKESMAS UJUNG PADANG RASIAN, SOUTH ACEH DISTRICT - Lensoni, Lensoni; Lubis, Yuni Agnes; Setiawan, Heri; Hidayatullah, Muhammad; Naira, Alifya Zuriva (Transpublika Publisher, 2024)
According to the WHO, large amounts of mercury pollution can have adverse health effects. Mercury, with the symbol Hg and atomic number 80, is often used in gold processing as a binding agent. Observations in Pasie Raja Sub-district, South Aceh District, showed that gold processing there still uses amalgamation techniques involving mercury, which is toxic and harmful to health. This experimental study was conducted in the UPTD Puskesmas Ujung Padang Rasian, South Aceh District, in June 2023, with a focus on analyzing the surrounding wastewater. Samples were taken from 14 well points around the gold processing site. Laboratory analysis results showed no detection of mercury in the water samples. However, this may be due to the mercury concentration being very small and undetectable by the equipment. Based on these results, the mercury content in the well water samples is still in accordance with the quality standard set by Government Regulation No. 82 of 2001, with a threshold of 0.001 µg/l. Thus, well water in the working area of UPTD Puskesmas Ujung Padang Rasian was not detected to contain mercury because the concentration was too small to be detected by the instrument.